Studi Ulumul Qur’an Karya Muhammad Mafudz Al-Tarmas Dalam Buku Fath Al-Khabir Bi Sharh Miftah Al’Tafsir - Ihwan Fahidin (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
This research reviews the differentiation, uniqueness, and theoretical power that is in Fath al-Khabir bi Sharh Miftah al-Tafsir. This research is a manuscript research by Sheikh Muhammad Mahfudz al-Termasi Pacitan which explain/sharh the book of miftah al-Tafsir or what is called Alfiyah Ilm Tafsir written by Nigerian scholar named Syeih Abdullah ibn Muhammad ibn Uthman ibn Salih al-Niji ri. The book is a manuscript that is still in the form of Sheikh Mahfudz Termas’s handwriting, this study uses a philology method that will describe the manuscript and analyze it using several contemporary Qur’anic study theories. This research shows the concept of a unique and systematic ulumul Qur’an offered by Kyai Mahfudz Termas.